Advancing Sustainable Infrastructure Management: Insights from System Dynamics - Julio Juarez-Quispe; Erick Rojas-Chura; Alain Jorge Espinoza Vigil; Milagros Socorro Guillén Málaga; Oscar Yabar-Ardiles; Johan Anco-Valdivia; Sebastián Valencia-Félix (Buildings)
Rapid infrastructure growth in developing countries has intensified environmental challenges due to cost-prioritizing practices over sustainability. This study evaluates 21 identified sustainable-driving tools to improve the management of infrastructure throughout its life cycle, by interacting with 20 out of 36 key infrastructure system management variables (ISMVs). Using a systems thinking approach, a Sustainable Systems Dynamic Model (SSDM) is developed, comprising a nucleus representing the interconnected stages of the life cycle: planning and design (S1), procurement (S2), construction (S3), operation and maintenance (S4), and renewal and disposal (S5). The model incorporates a total of 12 balance (B) and 25 reinforcement (R) loops, enabling the visualization of critical interdependencies that influence the sustainability of the system. In addition, its analysis shows the interdependencies between variables and stages, demonstrating, for example, how the implementation of tools such as LCA, BIM, and Circular Economy principles in S1, or IoT and SHM in S4, significantly improve sustainability. A gap between theory and practice in the adoption of sustainable practices is identified, which is aggravated by the lack of knowledge in specific developing countries’ context. Hence, this study contributes to its closure by offering a model that facilitates the understanding of key interactions in infrastructure systems.